Capacity design: Early history. (15th August 2018) - Fardis, Michael N.
Summary: The paper documents the little‐known story behind the development of the concept of capacity design and sheds new light regarding the individual contributions, which led to it becoming an important design tool for the control of inelastic response. The basic concept was laid out in the 1961 book by Blume, Newmark, and Corning, Design of Multistory Reinforced Concrete Buildings for Earthquake Motions, with the notable sections written by Mete Sozen; the basic concept was included in the 1967 to 1968 revision of the Structural Engineers Association of California (SEAOC) recommendations. John Hollings, a prominent structural designer in New Zealand, quoted the SEAOC recommendations and Blume, Newmark, and Corning when he used these ideas in a design procedure he proposed in 1968 to 1969 for the control of the inelastic response in concrete buildings. The term "capacity design" for that procedure seems to have been coined by a select team of structural designers of New Zealand's public buildings under the leadership of Otto Glogau, who had already introduced the new SEAOC rules in the 1968 New Zealand design code for public buildings. Tom Paulay is credited with publicizing and further development of capacity design as a holistic approach for the control of inelastic response. He was instrumental in disseminating the concept, especially in Europe, and often is called the "father" of capacity design.